The moderating role of emotional intelligence in the relationship between foreign language enjoyment and english achievement among chinese ethnic minority college students: A theoretical perspective - Mingxing Li; Asmaa AlSaqqaf (ResearchGate, 2024)
This paper proposes emotional intelligence as a moderator in the relationship between English-as-a-foreign language enjoyment and English achievement within the Chinese multilingual context. While foreign language enjoyment serves as the independent variable facilitating English learning, English achievement plays a dependent role in this relationship. Meanwhile, emotional intelligence acts as a moderator that can enhance, diminish, or modify the relationship between English foreign language enjoyment and English achievement. High emotional intelligence enhances learners’ ability to harness positive emotions for sustained motivation and engagement, equips them with effective coping mechanisms, and promotes meaningful social interactions. As a result, learners with high emotional intelligence are more likely to experience greater success and proficiency in English achievement through their enhanced capacity to leverage the benefits of foreign language enjoyment. This paper employs a quantitative approach and utilises questionnaires on emotional intelligence, foreign language enjoyment, and English achievement data to examine the relationship and interplay among 382 ethnic minority college students in China. The study highlights the importance of fostering emotional intelligence and positive affective experiences in the EFL classroom, suggesting that an engaging and enjoyable learning environment contributes to enhanced English achievement.